Implementasi Prinsip Pedagogi Sosial dalam Pendampingan Anak Korban Kekerasan Seksual di UPTD PPA Kota Semarang - Silvia Lutfiatunnisa'; Decky Avrilianda (Universitas Al Azhar Indonesia, 2026)
Sexual violence against children is a national issue that requires immediate intervention. Although various existing studies focus on the stages of support, the appropriate approach to child victims of sexual violence is often overlooked. This study aims to examine the application of social pedagogy principles at the UPTD PPA Semarang City in providing support to child victims of sexual violence. The study used a descriptive qualitative method with research subjects including the Head of the UPTD, counselors, and psychologists. Data were collected through non-participant observation, semi-structured interviews, and document analysis, with data validity through triangulation of sources and techniques. Data analysis included collection, reduction, presentation and drawing conclusions. The results of the study indicate that the application of social pedagogy principles is seen in support tailored to the characteristics of children so that the professional services provided can integrate cognitive competencies, emotional sensitivity, and practical skills. The conclusion of this study is that the application of social pedagogy principles at the UPTD PPA Semarang City can improve the quality of support and assistance provided to child victims of sexual violence.Keywords - Mentoring, Sexual Violence, Social Pedagogy.